Corporatization of state owned press institutions in Egypt : an adapted corporate governance index - Eldaba, Diana Samir (AUC Knowledge Fountain, 2015)
This study analyzes the published corporate governance guidelines and related documents of the BBC, The New York Times, The Washington Post, The Guardian Media Group and Thomson Reuters and accordingly creates an adapted corporate governance index suitable for implementation on the state-owned press institutions in Egypt with the aim of moving them towards a greater degree of corporatization. The notion of the research is that the legislations and board structures of state owned press institutions in Egypt don’t fit their mandate and that corporate governance needs to be applied to these institutions to make them eligible for market. Qualitative content analysis is applied to the studied documents and in depth interviews are conducted with ten media and academic experts to realize the proposed index. The study adopts three justified approaches, public interest, stakeholders’ benefit and agency governance approaches. The index is then applied as an assessment tool to Al-Ahram state owned press institution.